Historical phosphorus dynamics in Lake of the Woods (USA–Canada) — does legacy phosphorus still affect the southern basin?. (2nd October 2017) - Edlund, Mark B.; Schottler, Shawn P.; Reavie, Euan D.; Engstrom, Daniel R.; Baratono, Nolan G.; Leavitt, Peter R.; Heathcote, Adam J.; Wilson, Bruce; Paterson, Andrew M.
ABSTRACT: Edlund MB, Schottler SP, Reavie ED, Engstrom DR, Baratono NG, Leavitt PR, Heathcote AJ, Wilson B, Paterson AM. 2017. Historical phosphorus dynamics in Lake of the Woods (USA–Canada) — does legacy phosphorus still affect the southern basin? Lake Reserv Manage. 33:386–402. A historical phosphorus (P) budget was constructed for southern Lake of the Woods. Sediment cores from 7 bays were radioisotopically dated and analyzed for loss-on-ignition, P, Si, diatoms, and pigments. Geochemical records for cores were combined using focusing factors for whole-basin estimates of sediment, total P, and P fraction accumulation. Although historical monitoring shows that external P loads decreased since the 1950s, sediment P has continued to increase since the mid-20 th century. Much sediment P is labile and may be mobile within the sediments and/or available for internal loading and resuspension. Two mass-balance models were used to explore historical P loading scenarios and in-lake dynamics, a static one-box model and a dynamic multi-box model. The one-box model predicts presettlement external loads were slightly less than modern loads. The dynamic model shows that water-column P was higher in the 1950s–1970s than today, that the lake is sensitive to external loads because P losses from burial and outflow are high, and that the lake is moving to a new steady state with respect to water-column P and size of the active sediment P pool. The active sediment pool built up in the mid-20 th century has been depleted through outflow and burial, such that its legacy effects are now minimal. Comparison of historical nutrient dynamics and sediment records of algal production showed a counterintuitive increase in production after external P loads decreased, suggesting other drivers may now regulate modern limnoecology, including seasonality of P loading, shifting nutrient limitation, and climate warming.